Fibrin hydrogels promote scar formation and prevent therapeutic angiogenesis in the heart. (31st August 2020) - Melly, Ludovic; Grosso, Andrea; Stanciu Pop, Claudia; Yu‐Hsuan, Chu; Nollevaux, Marie‐Cécile; Schachtrup, Christian; Marsano, Anna; Di Maggio, Nunzia; Rondelet, Benoît; Banfi, Andrea
Abstract: Therapeutic angiogenesis is the delivery of factors to promote vascular growth and holds promise for the treatment of ischemic heart conditions. Recombinant protein delivery to the myocardium by factor‐decorated fibrin matrices is an attractive approach, thanks to the ability to precisely control both dose and duration of the treatment, the use of a clinically approved material like fibrin, and the avoidance of genetic modification. Here, we investigated the feasibility of inducing therapeutic angiogenesis in the rat myocardium by a state‐of‐the‐art fibrin‐based delivery platform that we previously optimized. Engineered versions of murine vascular endothelial growth factor A (VEGF164 ) and platelet‐derived growth factor BB (PDGF‐BB) were fused with an octapeptide substrate of the transglutaminase coagulation factor fXIIIa (TG) to allow their covalent cross‐linking into fibrin hydrogels and release by enzymatic cleavage. Hydrogels containing either 100 μg/mL TG‐VEGF alone or in combination with 10 μg/mL TG‐PDGF‐BB or no factor were injected into rat myocardium. Surprisingly, vascular density was severely reduced in all conditions, both in and around the injection site, where large fibrotic scars were formed. Scar formation was not due to the presence of growth factors, adaptive immunity to human proteins, damage from injection, nor to mechanical trauma from the hydrogel stiffness or volume. Rather scar was induced directly by fibrin and persisted despite hydrogel degradation within 1 week. These results caution against the suitability of fibrin‐based platforms for myocardial growth factor delivery, despite their efficacy in other tissues, like skeletal muscle. The underlying molecular mechanisms must be further investigated in order to identify rational targets to prevent this serious side effect.